Vibration Response Characteristics of Adjacent Tunnels under Different Blasting Schemes - Jianxin Yu; Zhibin Zhou; Xin Zhang; Xiaolin Yang; Jinxing Wang; Lianhao Zhou (Shock and Vibration)
The vibration caused by the tunnel blasting and excavation will harm the surrounding rock and lining structure of the adjacent existing tunnels. This paper takes a two-lane large-span highway tunnel as the research object, conducts on-site monitoring tests on the impact of vibration caused by the blasting and excavation of new tunnels on the existing tunnels under different blasting schemes, and analyses in detail the three-dimension vibration velocity by different excavation footages. From the vibration speed, it is concluded that the influence of the existing tunnel of the newly built tunnel blasting team is affected by various factors, such as distance, free surface, charge, and blasthole distribution. With different blasting schemes, the greater the amount of charge, the greater the vibration caused by blasting. Existing tunnels correspond to the front of the tunnel, and the axial and radial vibration peaks are greater than the vertical. Although the cut segment uses a less amount of explosive and has a less blasthole layout, there is only one free surface. Because of the clamping of the rock, it is compared with the other two segments. The vibration caused is the largest. Although the peripheral holes are filled with a large amount of explosive, the arrangement of the blast holes is relatively scattered and there are many free surfaces. Hence, the vibration caused is the smallest. Corresponding to the back of the tunnel face, since there is no rock clamp, the vibration caused by the cut segment is the smallest, and the vibration caused by the peripheral segment and the floor segment is relatively large. The vibration caused by the front explosion side is significantly greater than the vibration caused by the back explosion side. The vibration velocity caused by the unit charge of 1.5 m footage is greater than that of the 3.0 m footage. The vibration velocity caused by the unit charge of the cut segment is the largest, and the vibration velocity caused by the peripheral segment and the floor segment is smaller. The research results provide a reference for the blasting control of similar engineering construction.